2013
DOI: 10.5539/ass.v9n4p105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Socioeconomic Status on Emersion Adolescent Creativity

Abstract: Prior research has attempted to investigate creativity as a behavior resulting from the interaction between the cognitive abilities, social environment and personal characteristics, but very little research has look at the role of environment characteristics on Emersion Adolescent Creativity. Hence, this article focuses on the effect of socioeconomic status on emerging adolescent creativity. In other words, family economic status, father’s education and mother’s education are the three dimensions of socioecono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
9
1
3
Order By: Relevance
“…For example, Parsasirat et al . () revealed that family economic status and parent education were positively associated with children’s creativity. Similarly, Heinla () reported that children whose parents have university education, or work as top executives or specialists, tend to earn higher scores on creativity tests than those from low SES families.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, Parsasirat et al . () revealed that family economic status and parent education were positively associated with children’s creativity. Similarly, Heinla () reported that children whose parents have university education, or work as top executives or specialists, tend to earn higher scores on creativity tests than those from low SES families.…”
Section: Introductionmentioning
confidence: 98%
“…Family socioeconomic status (SES), usually considered as the sum scores awarded for education, occupation, and average monthly income of the parents, is one of the most remarkable features of family background (Bradley & Corwyn, 2002). Many studies have revealed that financially or culturally privileged children who are adopted into comparatively higher SES families, have more advantages for the fulfillment of creative abilities than lower SES children (Dudek & Runco, 1993;Hussain & Sajid, 1990;Lichtenwalner & Maxwell, 1969;Parsasirat, Foroughi, Yusooff, Subhi, Nen & Farhadi, 2013;Smith, 1965). For example, Parsasirat et al (2013) revealed that family economic status and parent education were positively associated with children's creativity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have attempted to research creativity as a behavior resulting from an interaction among cognitive abilities, individuality, and social environment, but few studies have examined the role of SES, such as family income, in creative thinking (Parsasirat et al, 2013). Recently, some scholars have begun to explore the relationship between family income and creativity.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have attempted to research creativity as a behavior resulting from an interaction 140 among cognitive abilities, individuality, and social environment, but few studies have examined 141 the role of SES, such as family income, in creative thinking (Parsasirat et al, 2013). Recently, 142 some scholars have begun to explore the relationship between family income and creativity.…”
mentioning
confidence: 99%